Effect of high dose inhaled beclomethasone dipropionate on carbohydrate and lipid metabolism in normal subjects. - Kruszynska, Y T (1987)
The metabolic effects of four weeks' high dose inhaled beclomethasone dipropionate (500 micrograms twice daily) were studied in nine normal subjects with an open study design. No effect was found on fasting blood glucose concentration or glycosylated haemoglobin concentration. Peak blood glucose concentration 30 minutes after a 75 g oral glucose load was, however, significantly higher (7.1 (SEM 0.2) versus 6.7 (0.1) mmol/l, or 128 (3.6) v 121 (1.8) mg/100 ml). After treatment there was a 36% increase in fasting serum insulin concentration (7.6 (0.7) versus 5.6 (0.5) mU/l) and a 32% increase in the area under the serum insulin concentration curve after glucose challenge. High dose inhaled beclomethasone dipropionate treatment raised the fasting plasma cholesterol concentration (4.62 (0.25) v 4.16 (0.26) mmol/l, or 178 (9.7) v 161 (10.0) mg/100 ml) and high density lipoprotein cholesterol (1.19 (0.065) versus 0.97 (0.065) mmol/l, or 45 (2.5) v 37 (2.5) mg/100 ml). Fasting blood lactate and pyruvate concentrations were also significantly higher and blood glycerol lower. The findings indicate that high dose inhaled beclomethasone dipropionate may disturb both carbohydrate and lipid metabolism.